Human somatic cells acquire the plasticity to generate embryoid-like metamorphosis via the actin cytoskeleton in injured tissues (2016)
Emergent biological responses develop via unknown processes dependent on physical collision. In hypoxia, when the tissue architecture collapses but the geometric core is stable, actin cytoskeleton filament components emerge, revealing a hidden internal order that identifies how each molecule is reassembled into the original mold, using one common connection, i.e., a fractal self-similarity that guides the system from the beginning in reverse metamorphosis, with spontaneous self-assembly of past forms that mimics an embryoid phenotype. We captured this hidden collective filamentous assemblage in progress: Hypoxic deformed cells enter into intercellular collisions, generate migratory ejected filaments, and produce self-assembly of triangular chiral hexagon complexes; this dynamic geometry guides the microenvironment scaffold in which this biological process is incubated, recapitulating embryonic morphogenesis. In all injured tissues, especially in damaged skeletal (striated) muscle cells, visibly hypertrophic intercalated actin-myosin filaments are organized in zebra stripe pattern along the anterior-posterior axis in the interior of the cell, generating cephalic-caudal polarity segmentation, with a high selective level of immunopositivity for Actin, Alpha Skeletal Muscle antibody and for Neuron-Specific Enolase expression of ectodermal differentiation. The function of actin filaments in emergent responses to tissue injury is to reconstitute, reactivate and orchestrate cellular metamorphosis, involving the re-expression of fetal genes, providing evidence of the reverse flow of genetic information within a biological system. The resultant embryoid phenotype emerges as a microscopic fractal template copy of the organization of the whole body, likely allowing the modification and reprogramming of the phenotype of the tumor in which these structures develop, as well as establishing a reverse primordial microscopic mold to collectively re-form cellular building blocks to regenerate injured tissues. Tumorigenesis mimics a self-organizing process of early embryo development. All malignant tumors produce fetal proteins, we now know from which these proteins proceed. Embryoid-like metamorphosis phenomena would represent the anatomical and functional entity of the injury stem cell niche. The sufficiently fast identification, isolation, culture, and expansion of these self-organized structures or genetically derived products could, in our opinion, be used to develop new therapeutic strategies against cancer and in regenerative medicine. © 2016, E-Century Publishing Corporation. All rights reserved.